Bottom-up synthetic immunology - Göpfrich, Kerstin; Platten, Michael; Frischknecht, Friedrich; Fackler, Oliver T. (Nature nanotechnology, 2024)
Infectious diseases and cancer evade immune surveillance using similar mechanisms. Targeting immune mechanisms using common strategies thus represents a promising avenue to improve prevention and treatment. Synthetic immunology can provide such strategies by applying engineering principles from synthetic biology to immunology. Synthetic biologists engineer cells by top-down genetic manipulation or bottom-up assembly from nanoscale building blocks. Recent successes in treating advanced tumours and diseases using genetically engineered immune cells highlight the power of the top-down synthetic immunology approach. However, genetic immune engineering is mostly limited to ex vivo applications and is subject to complex counter-regulation inherent to immune functions. Bottom-up synthetic biology can harness the rich nanotechnology toolbox to engineer molecular and cellular systems from scratch and equip them with desired functions. These are beginning to be tailored to perform targeted immune functions and should hence allow intervention strategies by rational design. In this Perspective we conceptualize bottom-up synthetic immunology as a new frontier field that uses nanotechnology for crucial innovations in therapy and the prevention of infectious diseases and cancer. This Perspective highlights bottom-up molecular engineering and modular nanobiotechnological approaches for developing effective immunotherapeutics and their potential in personalized medicine.